A gate-tunable single-molecule diode. Issue 16 (13th April 2016) - Perrin, Mickael L.; Galán, Elena; Eelkema, Rienk; Thijssen, Joseph M.; Grozema, Ferdinand; van der Zant, Herre S. J.
Abstract : In the pursuit of down-sizing electronic components, the ultimate limit is the use of single molecules as functional devices. Abstract : In the pursuit of down-sizing electronic components, the ultimate limit is the use of single molecules as functional devices. The first theoretical proposal of such a device, predicted more than four decades ago, is the seminal Aviram–Ratner rectifier that exploits the orbital structure of the molecule. The experimental realization of single-molecule rectifiers, however, has proven to be challenging. In this work, we report on the experimental realization of a gate-tunable single-molecule rectifier with rectification ratios as high as 600. The rectification mechanism arises from the molecular structure and relies on the presence of two conjugated sites that are weakly coupled through a saturated linker. The observed gate dependence not only demonstrates tunability of the rectification ratio, it also shows that the proposed rectification mechanism based on the orbital structure is operative in the molecule.